LO53: Emergency department visits for hyperglycemia: through the eyes of the patient. (May 2020) - Yan, J.; Azzam, D.; Liu, S.; Spaic, T.; Columbus, M.; Van Aarsen, K.; Shepherd, L.
Abstract : Introduction: Patients with poorly-controlled diabetes often visit the emergency department (ED) for treatment of hyperglycemia. While previous qualitative studies have examined the patient experience of diabetes as a chronic illness, there are no studies describing patients' perceptions of ED care for hyperglycemia. The objective of this study was to explore the patient experience regarding ED hyperglycemia visits, and to characterize perceived barriers to adequate glycemic control post-discharge. Methods: This study was conducted at a tertiary care academic centre in London, Ontario. A qualitative constructivist grounded theory methodology was used to understand the experience of adult patient partners who have had an ED hyperglycemia visit. Patient partners, purposively sampled to capture a breadth of age, sex, disease and presentation frequency were invited to participate in a semi-structured individual interview to probe their experiences. Sampling continued until a theoretical framework representing key experiences and expectations reached sufficiency. Data were collected and analyzed iteratively using a constant comparative approach. Results: 22 patients with type 1 or 2 diabetes were interviewed. Participants sought care in the ED over other options because of their concern of having a potentially life-threatening condition, advice from a healthcare provider or family member, or a perceived lack of convenient alternatives to the ED based on time and location. Participants' care expectations centred around symptom relief, glycemic control, reassurance and education, and seeking referral to specialist diabetes care post-discharge. Finally, perceived system barriers that challenged participants' glycemic control included affordability of medical supplies and medications, access to follow-up and, in some cases, the transition from pediatric to adult diabetes care. Conclusion: Patients with diabetes utilize the ED for a variety of urgent and emergent hyperglycemic concerns. In addition to providing excellent medical treatment, ED healthcare providers should consider patients' expectations when caring for those presenting with hyperglycemia. Future studies will focus on developing strategies to help patients navigate some of the barriers that exist within our current limited healthcare system, enhance follow-up care, and improve short- and long-term health outcomes.